The Hajj: Hazards of Heat Exposure and Prevalence of Heat Illnesses among Pilgrims - Qari, Suhaila (Journal of Liaquat University of Medical & Health Sciences, 2019)
Hajj, annually hosted by Saudi Arabia, is considered a religious major mass gathering event that pose significant public health challenges like the transmission of infectious diseases and illnesses related to climate change. Heat stress is a key problem that faced by about two and half millions pilgrims during Hajj. It has historically experienced high morbidity and mortality due to heat illnesses. The highest incidence of mortalities attributed to heat illnesses happened in 1409 Hijri and 1412 Hijri Hajj as the recorded maximum temperatures reached 48.7°C and 47.6°C respectively. Holy Makkah area had the highest recoded incidence of these mortalities, since pilgrims stay much longer periods in Makkah compared to Arafat and Mina. This work aimed to review the prevalence of heat illness in general and heat stroke in specific among the pilgrimage during Hajj and summarize the reasons that make pilgrimage more liable to develop heat stroke. This review also describes, in brief, the process of acclimatization to heat stress and the impact of heat stress on the body besides summarizing the common clinical presentation of heat stroke.